Experimental pleural empyema model in rabbits: Why, how and what are the next steps - Cvijanović, Vlado; Vojvodić, Danilo; Djurđević, Dragan; Jović, Milena; Stanić, Vojkan; Sekulović, Leposava; Perić, Tijana (Vojnosanitetski pregled, 2014)
Bacgraund/Aim. The use of new therapeutic methods to prevent development of fibrothorax as the final complication of the human pleural infections requires research with experimental animals. The aim of this study was to standardize the procedures for the establishment of our own experimental model of empyema in rabbits, since it should be able to offer similar conditions found in human pleural infections. Methods. This experiment included 15 chinchilla rabbits, weighing from 2.3 to 2.8 kg. There were 12 rabbits in the experimental group, while 3 rabbits formed the control group. On the first day, we administered 0.4–0.5 mL of turpentine in the right pleural space of the rabbits from the experimental group in order to provoke sterile exudative pleurisy. After 24 h we injected 1 mL of Staphylococcus aureus and 1 mL of Escherichia coli bacteria in the same concentration of 4.5 ´ 108 bacteria/mL. Thoracocentesis for the pleural fluid analysis was performed 24, 48, 72, and 96 h after bacteria instillation. In these pleural samples we estimated the number of leucocytes and the values of lactate dehydrogenase (LDH), glucose and pH in pleural fluid, as well as the presence of bacteria. We did not protect the animals with antibiotics, and on the day 7 of the experiment they were sacrificed with the lethal dose of barbiturate (iv). The lung from the empyemic side of all experimental animals and the lung of one control animal were histopathologically examined. Results. A total of 4 animals had a small amount of clear pleural fluids or there was no fluid obtained with thoracocentesis 24 and 48 h after the bacteria instillation. In the remaining 8 rabbits 24 h after bacteria administration the mean values (± SD) of the parameters monitored were as follows: Le 34.75 ± 6.13 ´ 109/L, LDH 17,000 ± 4,69 U/L, glucose 1.23 ± 0.45 mmol/L, and pH 6.975 ± 0.15. The obtained values met the criteria for the evaluation of effusion as pleural empyema or complex and complicated pleural effusion (LDH > 1000 U/L, glucose < 2.31 mmol/L and pH < 7.20). Bacterial cultures were positive in 5 out of 8 first pleural samples and in only 2 samples after 48 h of bacteria administration. There was a positive correlation between the number of leukocytes and the LDH value (r = 0.071, p < 0.001), and a negative correlation between the number of leukocytes and the glucose level (r = 0.864, p < 0.001), and the leukocytes number and pH of the pleural fluid (r = 0.894, p < 0.001). The mean glucose value increased after 48 h (3.23 ± 0.44 mmol/L), and the pH value rose after 72 h (7.22 ± 0.03) which was beyond the empyema level. Conclusion. The creation of the experimental empyema model is a very delicate work with uncertain success. Its value and importance are crucial for pleural pathology research. With the intention to obtain a more empyemic pleural reaction we created a model with two different human pathogen bacteria. We generated the satisfactory results, but not as good as those contained in some of the reference literature data.